Perlindungan Konsumen terhadap Helm Non-SNI dalam Perspektif Maqashid Syariah: Studi Kasus di Kecamatan Medan Perjuangan - Annisa Febrianti Aryet; Harahap, Abd.Rahman (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze consumer protection against non-SNI (Indonesian National Standard) helmets from the perspective of maqashid syariah, with a case study in Medan Perjuangan District. Helmets that do not meet SNI standards pose potential risks to user safety, raising issues concerning consumers' rights to safety and security. In maqashid syariah, the protection of life (hifz al-nafs) is a fundamental objective that must be upheld in society. This research employs a qualitative approach with a case study method, involving in-depth interviews with consumers, producers, and authorities, as well as data analysis from relevant legal documents. The findings reveal that the lack of consumer awareness regarding the importance of SNI helmets, weak regulatory enforcement, and the widespread circulation of non-SNI helmets are key factors influencing consumer protection. From the perspective of maqashid syariah, the use of non-SNI helmets not only violates the principle of protecting life but also contradicts the principle of public welfare. Therefore, a collaborative effort between the government, manufacturers, and the community is necessary to enhance consumer education, strengthen regulatory oversight, and promote SNI-compliant helmets as a practical application of Islamic values in daily life.